The influences of China's Cultivated Land Fertility Protection Subsidy policy on farmers' agro-eco-environmental protection behavior: an application of the extended theory of planned behavior - Ting Liu; Linwei Du; Jiaona Hou; Xiancheng Zeng; Wenyan Zhang; He Xu (Journal of Environmental Management, 2025)

Synergizing awareness and policy: A system dynamics approach to reducing illegal waste dumping - Linwei Du; Ruidong Chang; Hongping Yuan; Jian Zuo; George Zillante (Environmental Development, 2025)

Public participation of illegal dumping management: mining of web based data - Linwei Du; Jian Zuo; Jixuan Han (Journal of Environmental Management, 2025)

A systematic review of PET circularity technologies and management strategies: Challenges and future directions - Jixuan Han; Jian Zuo; George Zillante; Ruidong Chang; Linwei Du (Resources, Conservation and Recycling, 2025)

Converting plastic waste into wood-plastic composite products – A practical environmental impacts assessment using primary data - Liancheng Li; Jian Zuo; Ruidong Chang; Linwei Du (Resources, Conservation and Recycling, 2025)

What influences the on-site recycling behaviour of C&D plastic waste in Australia? An action determination model approach - Liancheng Li; Jian Zuo; Linwei Du; Ruidong Chang (Journal of Environmental Management, 2024)

Records of Fukushima accident-derived cesium-137 in the Chukchi Sea sediment: Implication for a new time marker? - Xu Ren; Jinlong Wang; Gi Hoon Hong; Linwei Li; Qiangqiang Zhong; Dekun Huang; Tao Yu; Jinzhou Du (Science China Earth Sciences, 2024)

Understanding the metabolism and scaling law in construction projects: Evidence from China - Xiaowei Zou; Shuhui Tan; Jingke Hong; Linwei Du; Qingyue Zhao; Jian Zuo (Environmental Impact Assessment Review, 2024)

Automatic identification of illegal construction and demolition waste landfills: A computer vision approach - Qiaoqiao Yong; Huanyu Wu; Jiayuan Wang; Run Chen; Bo Yu; Jian Zuo; Linwei Du (Waste Management, 2023)

Assessing and predicting the illegal dumping risks in relation to road characteristics - Linwei Du; Jian Zuo; John Vanzo; Ruidong Chang; George Zillante (Waste Management, 2023)

Transnational recycling of Australian export waste: An exploratory study - Linwei Du; Jian Zuo; Kyle O'Farrell; Ruidong Chang; George Zillante; Liancheng Li (Resources, Conservation and Recycling, 2023)

Distinguishing the main components of submarine groundwater and estimating the corresponding fluxes based on radium tracing method—taking the Maowei Sea for example - Linwei Li; Jinzhou Du; Xilong Wang; Yanling Lao (Acta Oceanologica Sinica, 2023)

Effectiveness of solid waste management policies in Australia: An Exploratory Study - Linwei Du; Jian Zuo; Ruidong Chang; George Zillante; Liancheng Li; Anthony Carbone (Environmental Impact Assessment Review, 2023)

Alkalinity export to the ocean is a major carbon sequestration mechanism in a macrotidal saltmarsh - Yvonne Y.Y. Yau; Pei Xin; Xiaogang Chen; Lucheng Zhan; Mitchell Call; Stephen R. Conrad; Christian J. Sanders; Linwei Li; Jinzhou Du; Isaac R. Santos (Limnology and Oceanography, 2022)
Saltmarshes are a blue carbon ecosystem accumulating large quantities of organic carbon in sediments. Some of this carbon can be transformed into dissolved inorganic carbon (DIC) and methane (CH 4 ) that may eventually be exported to the ocean or atmosphere. Although extensive studies have quantified specific components of the carbon budget such as carbon burial, limited attention has been given to pore‐water‐derived carbon and total alkalinity (TA) exports to the ocean. Here, we quantified lateral exports to the ocean (outwelling) of 202 ± 160 and 78 ± 75 mmol m −2 d −1 of DIC and TA, respectively. The TA : DIC concentration ratio in the creek waters was ~ 1, implying TA production from anaerobic mineralization in sediments. The lateral TA exports were comparable to the local (94 ± 48 mmol m −2 d −1 ) and national (~ 50 mmol m −2 d −1 ) organic carbon burial. High TA exports could locally increase the ocean buffering capacity and contribute bicarbonate to the coastal ocean, acting as a long‐term carbon storage. Pore water traced by radon contributed 28–37% and 58–69% of DIC and TA exports. Separating the two major DIC components (i.e., CO 2 emissions and alkalinity exports) is essential to resolve the carbon sequestration potential from saltmarshes. Here, dissolved CO 2 emissions to the atmosphere accounted for 3–5% of total DIC outwelling. CH 4 emissions played a minor role offsetting around 0.3 to 6% of the carbon sequestration. Overall, we demonstrate that alkalinity export into the ocean can be an overlooked carbon sequestration pathway in saltmarshes at rates comparable to carbon burial.

Contrasting behaviors of 210Po, 210Pb and 234Th in the East China Sea during a severe red tide: Enhanced scavenging and promoted fractionation - Qiangqiang Zhong; Linwei Li; Viena Puigcorbé; Dekun Huang; Tao Yu; Jinzhou Du (Acta Oceanologica Sinica, 2022)

Estimating submarine groundwater discharge at a subtropical river estuary along the Beibu Gulf, China - Xilong Wang; Kaijun Su; Juan Du; Linwei Li; Yanling Lao; Guizhen Ning; Li Bin (Acta Oceanologica Sinica, 2021)

An approach to evaluation of environmental benefits for ecological mining areas based on ant Colony algorithm - Linwei Wan; Chenlin Du (Earth Science Informatics, 2021)